Romifidine alone and in combination with ketamine in sheep - SHARMA, A K; SHAHI, APRA; KUMAR, NAVEEN; MAITI, S K (The Indian Journal of Animal Sciences, 2011)
Healthy sheep (10) were divided into equal groups 1and 2. The onset of action of after administration of romifidine (10 !lg kg-I) occurred within. 1.5 min. It induced sedation (mild to moderate), analgesia (mild) and motor incordination, which was sufficient to perform non- invasive procedures in sheep. In group 2, romifidine-ketamine combination produced anaesthesia of 17.25Â±4.60 min. Muscle relaxation and analgesia was excellent during peak effect. Bradycardia was recorded in both groups which was significant up to 20 min in group 1. Rapid, shallow and apneustic breathing pattern was observed during maximum effect of drugs. Changes in hemato-biochemical parameters were transient. Initial significant increase in mean arterial pressure and central venous pressure was seen in both groups. Electrocardiograms revealed sino atrial block in 3 sheep (3060 min), II degree AV block, sinus arrhythmia (90-120 min), increase PR interval and increase QT interval. Recovery was smooth and uncomplicated in both groups.Â